2013
DOI: 10.4070/kcj.2013.43.8.550
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Internal Carotid Artery Stenosis in Patients with Abdominal Aortic Aneurysm

Abstract: Background and ObjectivesAbdominal Aortic Aneurysm (AAA) and carotid disease have medical and social significance, considering their morbidity, disability, and economic consequences. The study objectives were to determine the prevalence of asymptomatic internal carotid artery (ICA) lesions ≥70% in patients with AAA, the correlation of AAA diameter with the degree of ICA stenosis and symptoms, and the importance of preventive ultrasound checkups.Subjects and MethodsA prospective non-randomized controlled study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Few studies 3,9,11,[15][16][17] investigated the prevalence of asymptomatic CAD or CeVD in patients with AAA. In a previous study, 3 the prevalence of significant CAD in patients with AAA was 71%, but this study included patients with previous MI and patients with typical angina pectoris.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies 3,9,11,[15][16][17] investigated the prevalence of asymptomatic CAD or CeVD in patients with AAA. In a previous study, 3 the prevalence of significant CAD in patients with AAA was 71%, but this study included patients with previous MI and patients with typical angina pectoris.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 This observation has implications for identification and treatment of underlying CAD before elective repair of AAAs, emphasizing the need of strategies for asymptomatic CAD and CeVD detection in patients with AAA. [8][9][10][11] Yet, the role of coronary angiography or noninvasive CAD or CeVD screening in patients with AAA without symptoms or history of CAD or CeVD is currently uncertain. These patients may have asymptomatic high risk of CAD or CeVD that should need prompt revascularization according to guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…A series of 757 patients with CABG showed a 26.4 % rate of moderate carotid stenosis and an 8.6 % rate of severe carotid stenosis [13]. Among patients with abdominal aortic aneurysms, severe asymptomatic carotid stenosis has been seen in 10.8 % [14].…”
Section: Epidemiologymentioning
confidence: 98%
“…Kurvers et al [34] reported the prevalence of an internal carotid artery stenosis (ICAS) >70% in 8.8% of persons with AAA and recommended ICAS screening for AAA patients. In another study, the ICAS prevalence in patients with AAA was calculated at 10.8%, as a consequence of which preprocedural duplex sonography was recommended [35]. Reference can be made to the joint recommendation of the German Society for Anesthesiology and Intensive Care Medicine, the German Society of Surgery and the German Society of Internal Medicine for the preoperative evaluation of adult patients prior to elective, non-cardiothoracic surgery [36].…”
Section: Sonography Of Cervical Vesselsmentioning
confidence: 99%